2015
DOI: 10.18632/oncotarget.4067
|View full text |Cite
|
Sign up to set email alerts
|

p53 attenuates AKT signaling by modulating membrane phospholipid composition

Abstract: The p53 tumor suppressor is the central component of a complex network of signaling pathways that protect organisms against the propagation of cells carrying oncogenic mutations. Here we report a previously unrecognized role of p53 in membrane phospholipids composition. By repressing the expression of stearoyl-CoA desaturase 1, SCD, the enzyme that converts saturated to mono-unsaturated fatty acids, p53 causes a shift in the content of phospholipids with mono-unsaturated acyl chains towards more saturated phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Previous work has shown that SREBP-1 is activated through several mechanisms including, regulation by the PTEN/PI3K/Akt/mTOR pathway 20 , 44 , p53 19 , 45 , modulation of MAPK signaling by KRAS 46 and by direct SREBP phosphorylation by Erk1/2 47 , 48 . Our work identifies mutant BRAF as another key modulator of SREBP-1 processing and function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that SREBP-1 is activated through several mechanisms including, regulation by the PTEN/PI3K/Akt/mTOR pathway 20 , 44 , p53 19 , 45 , modulation of MAPK signaling by KRAS 46 and by direct SREBP phosphorylation by Erk1/2 47 , 48 . Our work identifies mutant BRAF as another key modulator of SREBP-1 processing and function.…”
Section: Discussionmentioning
confidence: 99%
“…MYC is often amplified in lung SCC [ 20 , 21 ] and we found evidence from the UCSC genome browser that ELOVL6 expression is controlled by MYC ( Supplementary Figure S6 ). TP53, which is often mutated in lung cancer [ 22 ], was recently shown to repress the transcription factor SREBP1c and accordingly several ELOVLs [ 29 ]. Besides changes in the expression of ELOVLs, an increase in substrate availability could drive the elongation process in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, the role of wild type p53 was examined in HCT116 cell line [71]. (This cell line was also used in the previous study and had a predominance of C36 and C34 carbons in their PI lipids [11]).…”
Section: Fatty Acyl Composition Of Phosphatidylinositol In Cancer Cellsmentioning
confidence: 99%
“…18:1/18:1) to either saturated or mono-unsaturated. These changes were most prominent in the PI species[71]. The increase in p53 resulted in a decrease in both PI(4,5)P2 and PI(3,4,5)P3.…”
mentioning
confidence: 91%